Analysis of First Language Acquisition in Padang Jambu Hamlet, Bawean Island, Gresik Regency (Psycholinguistic Study) - Najwa, Siti (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2023)
This study aims to identify and examine the acquisition of the first language in children at an early age in the process of language acquisition through what is heard and practiced with the language of the words they have. This study uses a qualitative descriptive research design because this research describes the results of research based on facts that exist in the daily life of the speakers and the process of acquiring language in the phonological aspects of children obtained from respondents to the research. Data collection is obtained from the results of recording, noting, observing, and documentation. The results of this study indicate that the object has mastered the vowel letters. From the description above, it can be concluded that the acquisition of language in children in the phonological aspect is influenced by the environment, especially their families, which is marked by the large amount of vocabulary they get in the family environment and around them. Even children can say some words, such as nouns, adjectives, and verbs.